Optimising Gelling Agents, Light Source and After-care to Commercialise Teak Tissue Culture (Plant Tissue Culture and Biotechnology, 2018)
Mass propagation of Teak (Tectona grandis Linn. f.) a commercial species is a priority to increase multiplication rate and meet the growing demand for planting material. The present study has assessed the in vitro performance of Teak Tissue Cultures with different gelling agents, different light conditions, and aftercare of ex vitro rooted shoots to enhance their survival rate. Multiple shoot formation was induced from excised seedling nodal explants on MS supplemented with BA and Kn and about 5 - 10 shoots were obtained from each explant. Significant variation (p > 0.05) was observed in the number of shoots produced by the different clones. Three gelling agents (agar, phytagel and gellan gum), and two light sources (tube light and LED) were tested for enhancing shoot multiplication. No significant difference in in vitro growth was observed between clones with different solidifying agents. Teak, however, did not respond favourably to LED lights. Rooting-acclimatization phase was achieved in the nursery with 80 - 95 per cent success. The rooted plants were sprayed with DAP and Humaur to assess the growth performance following transplanting. Significant variations in rooting indicate the existence of physiological variations among the clones. Application of fertilizers promoted an initial boost followed by a steady increase during the rest of the study period. Clones with high multiplication rates under in vitro conditions could be selected for commercialization of teak multiplication. Under ex vitro conditions, a spray of fertilizers during the initial establishment phase would result in increased vigour of transplantable plants. This would ensure better survival on out planting.Plant Tissue Cult. & Biotech. 28(1): 13-24, 2018 (June)